The Development of Plant Physiology Practicum Guidelines Based on Learning by Research for Biology Education Students - Thahir, Rahmatiah (Journal of Biology Education, 2021)
research college. Scientific attitudes, scientific processes, and scientific products are special characteristics of the research learning process. The three components of research learning are developed by educators, both teachers and lecturers, maximally in practicum activities in the laboratory. Therefore, as a first step in student learning, lecturers should be able to innovate and be creative in utilizing existing resources for example by the preparation and implementation practicum based on learning by research model. The purpose of this study is to know the process of developing a practicum guideline of Plant Physiology based on Learning By Research. To produce practical products of plant physiology that is valid, and practical for use in the Biological Education Program of Universitas Muhammadiyah Makassar. This research is Research and Development (R&D) with using plomp development model. From the results of the research that has been done shows that the practicum guide of Plant Physiology based on Learning by Research that has been developed meets valid and practical criteria. The validation result of the guide is obtained the average value of the Content Validation Coefficient of 0.88 or has high relevance. While the practicality test is in the category of 'overall implemented' with a value of 3.56.